Evaluation of Cell Block Quality in Cytodiagnosis of Body Fluids Effusion - Mohd Hafiiz, Mohamad Rizan; Suria Hayati, Md Pauzi; Azmawaty, Mohamed Nawi (2025)
Introduction: Conventional cytology smears and cell block techniques are routinely used for cytologic assessment of serous body effusion. Each technique shows varying diagnostic yield, cellular preservation and architectural assessment. This study aimed to evaluate the diagnostic quality of cytology smear slides and cell blocks prepared from serous effusion samples. Methodology: A total of 144 cases of serous body effusion with its concurrent cell block between year 2021 and 2023 were obtained. In each case, the slides of the conventional smears and its cell block were assessed using the Mair Scoring System to determine the outcomes of diagnostic quality. Unsatisfactory cytology cases were excluded from sampling. Result: The majority of cases were from pleural fluid (n= 98, 68.1%) followed by peritoneal (n=40, 27.8%) and pericardial fluid (n= 6, 4.2%). The highest proportion of samples were categorised as malignant effusion (56.3%). Diagnostically superior quality was mainly observed in conventional cytological smears (n=80) as compared to cell block section (n= 43). Furthermore, a high number of cell block samples were deemed diagnostically unsuitable (57 out of 144 samples, 40%). Statistical analysis showed a significant association between different preparation methods and diagnostic outcome (p < 0.001). Conclusion: The findings in this study emphasize the importance of good conventional smears and cell blocks in routine cytological examination. Since many cell block protocols are practiced worldwide, it is important for individual cytology laboratories to select the method most suitable for their needs, with ongoing quality monitoring.